PENGARUH KECERDASAN INTERPERSONAL TERHADAP PRESTASI BELAJAR MATEMATIKA - Asido Saragih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
This study aims to determine whether there is a positive and significant influence of interpersonal intelligence on mathematics learning achievement. This research was conducted at Strada Mardi Utama 1 Middle School, Jakarta in 2015. The method used was a quantitative-survey method. The samples used were 84 grade VIII students of SMP Strada Mardi Utama 1 Jakarta taken by random sampling or simple random sampling from two classes. Data analysis was performed using the correlation test, regression test, and ANOVA test. The results showed that there was a positive and significant influence of interpersonal intelligence on the mathematics achievement of Grade VIII students of SMP Strada Mardi Utama 1 Jakarta.